The Legitimacy Crisis of Customary Villages Under Indonesia’s Village Law - Sri Wahyu Kridasakti; Rina Elsa Rizkiana; Purwaningdyah Murti Wahyuni; Ni Made Jaya Senastri; Henny Yuningsih (Sriwijaya Law Review, 2025)
The absence of clear institutional linkages between bureaucratic villages (BVs) and customary villages (CVs) raises significant concerns regarding the legitimacy and effectiveness of their governance structures. Understanding the institutional relationship between these entities is therefore essential. This research analyses the legitimacy and legal implications of customary village regulations and investigates the disharmony between these regulations and Law Number 6 of 2014 in relation to the 1945 Constitution of the Republic of Indonesia (UUD 1945). Employing a socio-legal case study approach, this study focuses on five key sites: Gampong-Mukim in Aceh, Tosari-Tengger Village, Kanekes-Baduy, Tenganan Pegringsingan-Karangasem, and Pecatu-Badung. Legal materials were collected through document reviews and focus group discussions related to customary village governance. Findings reveal that Law Number 6 of 2014 concerning Villages fails to align with constitutional principles and shows inconsistencies when compared with regional regulations across the observed areas. Furthermore, the study identifies state intervention in customary village governance through the implementation of Law Number 6 of 2014—an approach deemed inappropriate unless such villages are fully and formally recognised. These regulatory inconsistencies and interventions undermine the legitimacy of Law Number 6 of 2014 in the context of customary village governance and threaten the autonomy and legal standing of Indonesia’s indigenous communities.